2016
DOI: 10.1002/biot.201500442
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical sensing system employing fructosamine 6‐kinase enables glycated albumin measurement requiring no proteolytic digestion

Abstract: Currently available enzymatic methods for the measurement of glycated proteins utilize fructosyl amino acid/peptide oxidases (FAOXs/FPOXs) as sensing elements. FAOXs/FPOXs oxidize glycated amino acids or glycated dipeptides but they are not able to accept longer glycated peptides or intact glycated proteins as substrates. Therefore, pretreatment via proteolytic digestion is unavoidable with the current enzymatic methods, and there remains a need for simpler measurement methods for glycated proteins. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…[62] Kameya et al reported an enzyme-based GA biosensor using SPCE which can detect higher concentrations of GA, partially falling in the clinical relevant range, but not achieving measurement of the full GA clinical range. [68]…”
Section: Chronoamperometric Deposition Of Au Nps Is Done Bymentioning
confidence: 99%
“…[62] Kameya et al reported an enzyme-based GA biosensor using SPCE which can detect higher concentrations of GA, partially falling in the clinical relevant range, but not achieving measurement of the full GA clinical range. [68]…”
Section: Chronoamperometric Deposition Of Au Nps Is Done Bymentioning
confidence: 99%
“…To overcome this issue, procedures that require no pre-digestion have been investigated. Kameya et al [ 100 ] exploited an enzyme retrieved from E. coli , fructosamine 6-kinase (FN6K) that can interact with intact GA; however, as pointed out by the authors, the reactions involved in this design require several additional steps and reagents (such as enzymes, co-substrates, buffers, mediators) that increase the complexity of the manufacturing and may lead to errors in the measurements. Table 3 compares the technologies presented.…”
Section: Glycated Albumin Analysismentioning
confidence: 99%
“…Several studies about the electrochemical biosensor for GA measurement have been reported using enzymes, antibody, aptamer or peptide as the biorecognition molecules and based on amperometry, electrochemiluminescence (ECL), impedance, voltammetry or field effect transistor (FET) as sensing principles [7,[16][17][18][19][20][21][22][23]. These studied are summarized in Table 1.…”
Section: Measurement Of Fructosyl Lysine and Ga With An Ide Enzyme Sementioning
confidence: 99%